2021
DOI: 10.1097/gox.0000000000003456
|View full text |Cite
|
Sign up to set email alerts
|

Salvaging the Unsalvageable: Negative Pressure Wound Therapy for Severe Infection of Prosthetic Breast Reconstruction

Abstract: Background: Severe infections of implant-based breast reconstruction are challenging to treat. Traditional management is removal of the implant with a further attempt at reconstruction months later once the infection has settled. This study evaluates an alternative management protocol using negative pressure wound therapy with instillation (NPWTi). Methods: Consecutive patients with severe peri-prosthetic infection following breast reconstruction were managed using the Impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Many other protocols also involve extended postoperative oral antibiotic regimens between 3 18 and 6 weeks 23 or more following operative salvage. Although all of our patients completed outpatient antibiotic regimens, none extended past 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many other protocols also involve extended postoperative oral antibiotic regimens between 3 18 and 6 weeks 23 or more following operative salvage. Although all of our patients completed outpatient antibiotic regimens, none extended past 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…changes. 9 , 15 , 16 , 18 Cheong et al reported a protocol in which V.A.C. VERAFLO was inserted for a total of 7 days before removal and placement of permanent implants; this week-long therapy involved foam changes in the operating room every 2 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations